Effect of salivary contamination on shear bond strength of two adhesives: An in vitro study - Shruti B Patil; Ashwini Tumkur Shivakumar; Shivani Shah (Wolters Kluwer Medknow Publications, 2014)
Introduction: Composite material used with bonding system are technique sensitive and contamination of an etched surface by saliva or blood plays a key role in bonding efficacy. Achieving good moisture control is a common problem encountered and is of importance while treating a pediatric age group since rubber dam in dental office is commonly applied in fewer than 10% of restorative treatment. Despite the advantage of rubber dam application, usage of rubber dam depends on child's behavior and its level of co-operation for which pediatric dentists compromise with its usage. This study was conducted to evaluate the effect of salivary contamination of enamel and dentin on bond strength of two adhesives. Materials and Methods: An in vitro study comprised of test group of 112 central incisors divided into 4 groups for testing on enamel and dentin separately. These are Group I: Control group without salivary contamination; Group II: Contaminated with saliva and air-dried; Group III: Contaminated with saliva, rinsed and air-dried; Group IV: Coated with adhesive, light cured and then contaminated. Shear bond strength was calculated using universal testing machine. Results: For testing on enamel and dentin, significantly decreased bond strength was seen with Group II (P < 0.05) and Group IV (P < 0.01) showed decreased bond strength, whereas bond strength of group III was not significant (P > 0.05), when compared with control Group I. Conclusion: The decontamination method used in this study by rinsing the contaminated cured adhesive layer that did not reverse the harmful effect of salivary contamination. As most of the children are active and restless with swinging mood, it is important not to negotiate with the procedural steps during treatment.